2019
DOI: 10.1111/1758-2229.12751
|View full text |Cite
|
Sign up to set email alerts
|

A microcin processing peptidase‐like protein of the cyanobacterium Synechococcus elongatus is essential for secretion of biofilm‐promoting proteins

Abstract: Summary Small secreted compounds, e.g. microcins, are characterized by a double‐glycine (GG) secretion motif that is cleaved off upon maturation. Genomic analysis suggests that small proteins that possess a GG motif are widespread in cyanobacteria; however, the roles of these proteins are largely unknown. Using a biofilm‐proficient mutant of the cyanobacterium Synechococcus elongatus PCC 7942 in which the constitutive biofilm self‐suppression mechanism is inactivated, we previously demonstrated that four small… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(33 citation statements)
references
References 42 publications
2
31
0
Order By: Relevance
“…Biofilms formed in standing cultures under the conditions indicated above and were quantified after 6 d growth as described (Parnasa et al, 2019), either by percentage of chlorophyll in suspension (Sendersky et al, 2017) or by crystal violet staining. For examination of biofilm formation in a flow cell system, initial cultures were diluted with BG-11 medium to OD750 of 1.0, and incubated for 48 h under 28˚C and 6 μmole photons*m −2 *s −1 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Biofilms formed in standing cultures under the conditions indicated above and were quantified after 6 d growth as described (Parnasa et al, 2019), either by percentage of chlorophyll in suspension (Sendersky et al, 2017) or by crystal violet staining. For examination of biofilm formation in a flow cell system, initial cultures were diluted with BG-11 medium to OD750 of 1.0, and incubated for 48 h under 28˚C and 6 μmole photons*m −2 *s −1 .…”
Section: Methodsmentioning
confidence: 99%
“…Studies of the molecular mechanisms underlying cyanobacterial biofilm development are currently emerging (Enomoto et al, 2014;Enomoto et al, 2015;Agostoni et al, 2016;Lacey and Binder, 2016;Enomoto et al, 2018). Our previous studies revealed a mechanism that represses biofilm formation in Synechococcus elongatus PCC 7942 (hereafter S. elongatus) (Schatz et al, 2013;Parnasa et al, 2016;Nagar et al, 2017;Sendersky et al, 2017;Parnasa et al, 2019). Inactivation of the gene Synpcc7942_2071 [recently designated as pilB (Yegorov et al, 2021)], which encodes an ATPase homologue of type II protein secretion (T2S) and/or type IV pilus assembly systems (T4P), impairs the inhibitory process, resulting in a mutant (PilB::Tn5) that develops robust biofilms (Schatz et al, 2013;Parnasa et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…In some cases, microcins require post-translational modifications to be active, and they do not require a lysis process to be secreted ( Baquero et al 2019 ). Microcin production has been reported in several Enterobacteriaceae and some cyanobacteria ( Rebuffat 2016 ; Parnasa et al 2019 ).…”
Section: Classification Mechanism Of Action and Structural Characteristicsmentioning
confidence: 99%
“…For example, four small secreted proteins, EbfG1-4 (enable biofilm formation with GG-motif), of S. elongatus PCC 7942 have been found to promote biofilm-formation. 16,17 Also, Synechocystis sp. PCC 6803 mutants lacking type IV pili (T4P) are unable to aggregate and form biofilms, 18 however, impairment of T4P formation in S. elongatus resulted in biofilm-forming-mutants, unlike the wild-type strain that grow planktonically.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, there have been advances in understanding biofilm formation by cyanobacteria. For example, four small secreted proteins, EbfG1‐4 (enable biofilm formation with GG‐motif), of S. elongatus PCC 7942 have been found to promote biofilm‐formation 16,17 . Also, Synechocystis sp.…”
Section: Introductionmentioning
confidence: 99%